VD_FINDINFO HC / 2010 / 132 vom 14. Dezember 2009 - VD Tribunal cantonal (2009)
SUCCESSION, DROIT FONCIER RURAL, EXPLOITATION AGRICOLE, VALEUR DE RENDEMENT, VALEUR VÉNALESENS GÉNÉRAL, INSOLVABILITÉ, DROIT AU GAIN | 615 CC, 617 CC, 619 CC, 620 al. 1 CC, 832 al. 2 CC, 489 CPC, 567 CPC, 586 CPC, 94 LDFR